Characterizing soil properties at different growth stages of sago plantation planted on mineral soil ecosystem - Nurul Hidayah, Binti Che Ali. (Universiti Malaysia Sarawak (UNIMAS), 2016)
Characterizing soil properties at sago palm (Metroxylon sagu) plantation on mineral soils ecosystem is important to provide fundamental information on soil fertility and suitability of the crops planted. The main objective for this research were to differentiate the mineral soil at fertilizing point and non-fertilizing point, to characterizing the mineral soil physicochemical properties in sago plantation at different growth stage (rosette and trunking) and to evaluate the influence of geographical factors and location on soils physicochemical properties. Study area was located at Mukah division; Sarawak with three different stations i.e. Senau, Oya and Sungai Talau. Senau and Oya were at rosette stage, while Sungai Talau at trunking stage. Undisturbed and composite soil samples were collected at the depth of 0-10cm and 30-40cm at both fertilizing point and non-fertilizing point. Moreover, soil hardness was measured using Hasegawa penetrometer. The result showed that, the mineral soil at fertilizing point and non-fertilizing point have no significant different. The physicochemical properties showed the different between SSSED Senau, SSSED Oya and Sungai Talau Research Station. Soil at SSSED Senau was resulted high salinity in average 844.25µS/cm. Meanwhile, SSSED Oya has higher pH value compared to SSSED Senau and Sungai Talau Research Station with average value 5.52. Sungai Talau Research Station showed high Total Carbon (T-C) with average value 111.33g/kg due to the high content of soil organic matter. Based on final finding of this study the mineral soil in sago plantation under SSSED program have been characterize under three different soil types which are Potential Acid Sulfate Soil (PASS), Alluvial soil and organic mineral soil. The geographical condition and location were resulted different soil physicochemical properties and influence the growth performance of sago palm. In this study the suitable area for sago palm plantation is at SSSED Oya because soil condition at SSSED Oya can promote growth performance of sago palm in next two to three years. Based on this study, the long term assessment and research study on sago palm might improve the growth performance and quality of sago palm.